2001
DOI: 10.2307/2673737
|View full text |Cite
|
Sign up to set email alerts
|

Provision of Hormonal Contraceptives without a Mandatory Pelvic Examination: The First Stop Demonstration Project

Abstract: Programs that provide hormonal contraceptives without requiring a pelvic examination can expand low-income women's access to these methods and improve the chances that they will obtain other reproductive health services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 4 publications
0
26
0
Order By: Relevance
“…Demonstration projects have shown that providing hormonal contraceptives without requiring a pelvic examination increases access to contraception and reproductive health services. Moreover, a majority of participating women feel that it is important to be able to begin contraception quickly and admit they associate pelvic examinations with fear and embarrassment [11].…”
Section: Discussionmentioning
confidence: 99%
“…Demonstration projects have shown that providing hormonal contraceptives without requiring a pelvic examination increases access to contraception and reproductive health services. Moreover, a majority of participating women feel that it is important to be able to begin contraception quickly and admit they associate pelvic examinations with fear and embarrassment [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, the routine pelvic examination is of limited utility as a screening test for ovarian cancer [26], and it is not recommended by the USPSTF [27]. In addition, results from demonstration projects indicated that women would value having this requirement waived [8,28]. …”
Section: Discussionmentioning
confidence: 99%
“…Prior studies on cervical cancer screening preferences suggest that some women place importance on the examination even if it is not effective for cancer screening, 10,11 but others may prefer not to undergo the examination, especially if it could lead to unnecessary intervention or interfere with access to contraception. 8,1214 …”
Section: Commentmentioning
confidence: 99%